Diagnostic criteria for exercise dependence in women. Issue 5 (26th September 2003) - Bamber, D J; Cockerill, I M; Rodgers, S; Carroll, D
Abstract : Objective: To formulate diagnostic criteria for exercise dependence. Method: Fifty six adult female exercisers were interviewed about their exercise behaviour and attitudes. The eating disorders examination, a semistructured clinical interview, was used to diagnose eating disorders. Interviews were taped, transcribed verbatim, and analysed from a social constructionist perspective using QSR NUD*IST. Participants also completed the exercise dependence questionnaire. Results: Two diagnostic criteria emerged from analysis of the interview data: impaired functioning and withdrawal. Impaired functioning was manifest in four areas: psychological, social and occupational, physical, and behavioural. Impairment in at least two areas was considered necessary for diagnosis. Withdrawal was evident as either an adverse reaction to the interruption of exercise or unsuccessful attempts at exercise control. Either sufficed for diagnosis. The absence or presence of an eating disorder was used to distinguish between primary and secondary exercise dependence. Ten women met these criteria for exercise dependence. All 10 also exhibited eating disorders and, accordingly, should be regarded as showing secondary, rather than primary, exercise dependence. Exercise dependent women had significantly higher scores on the exercise dependence questionnaire than non-dependent women. Conclusion: These new diagnostic criteria should now be adopted and explored further, particularly among men and individuals with possible primary exercise dependence.